2020
DOI: 10.1590/1679-395120190025x
|View full text |Cite
|
Sign up to set email alerts
|

“A word is enough to the wise?!”: a study on narratives produced by the media when translating the role of the players involved in the Operation Car Wash in Brazil

Abstract: Resumo O objetivo deste é artigo é analisar como a mídia traduz o papel dos envolvidos, os eventos, as relações, seus antecedentes e suas consequências, produzindo versões narrativas consumidas pela sociedade. É uma pesquisa de abordagem qualitativa, com base na análise de narrativas e na compreensão da construção social da realidade alicerçada nos sentidos articulados narrativamente pelos agentes. A partir de dados secundários coletados em três veículos de mídia - revistas Carta Capital, Veja e Exame, selecio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, some experts believe that there are times that anticorruption programs have yielded some positive results. An example of these programs is the "Lava Jato" (Operation Car Wash) anti-corruption program that led to the arrest and prosecution of hundreds of politicians and business executives in Brazil (Moro, 2018;Marona & Kerche, 2021;Seefeld & Rese, 2020). In essence, although there are high levels of corruption in Brazil, there is also some optimism that efforts to address the problem are producing some remarkable results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some experts believe that there are times that anticorruption programs have yielded some positive results. An example of these programs is the "Lava Jato" (Operation Car Wash) anti-corruption program that led to the arrest and prosecution of hundreds of politicians and business executives in Brazil (Moro, 2018;Marona & Kerche, 2021;Seefeld & Rese, 2020). In essence, although there are high levels of corruption in Brazil, there is also some optimism that efforts to address the problem are producing some remarkable results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, a study by Dammert (2012) identified a positive association between high crime rates and citizens’ perception of insecurity, suggesting that high crime enhances people's sense of insecurity in their neighborhood. Further studies also suggested that high crime rates lead to lack of trust and confidence in existing criminal justice systems such as the police and the courts (see Blanco & Ruiz, 2013; Singer et al, 2019). Ultimately, the lack of trust and confidence in the criminal justice system due to high crime rates coupled with perceived insecurity gives rise to issues of corruption (Engelmann, 2020; Paiva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%